2022
DOI: 10.1002/eer2.16
|View full text |Cite
|
Sign up to set email alerts
|

Seismic microzoning of the Delhi metropolitan area, India— I: Seismicity modeling

Abstract: Seismic activity parameters ( a $a$ and b $b$ values in a Gutenbdataer–Richter relationship, maximum magnitude M max ${M}_{\max }$, and predominant focal depths H $H$) have been estimated for a grid of square cells of size 0.1° in latitudes and longitudes covering a large region bound by 24°−33°N and 72°−82°E to define input seismicity for microzoning of the Delhi metropolitan area. For this purpose, seven area types of seismic sources are first identified from a detailed seismotectonic evaluation of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The major structural features in the IGP include numerous basement faults, ridges, and basins, such as the Great Boundary Fault, Moradabad Fault, Patna Fault, Lucknow Fault, Delhi‐Haridwar Ridge, Faizabad Ridge, and Munger‐Saharsa Ridge 53 . The IGP is characterized by much lower seismic potential than the Himalayan region, but the great Himalayan earthquakes may contribute significantly to the seismic hazard in this region also 54–56 …”
Section: Seismotectonic Setup and Strong‐motion Recording Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The major structural features in the IGP include numerous basement faults, ridges, and basins, such as the Great Boundary Fault, Moradabad Fault, Patna Fault, Lucknow Fault, Delhi‐Haridwar Ridge, Faizabad Ridge, and Munger‐Saharsa Ridge 53 . The IGP is characterized by much lower seismic potential than the Himalayan region, but the great Himalayan earthquakes may contribute significantly to the seismic hazard in this region also 54–56 …”
Section: Seismotectonic Setup and Strong‐motion Recording Sitesmentioning
confidence: 99%
“…53 The IGP is characterized by much lower seismic potential than the Himalayan region, but the great Himalayan earthquakes may contribute significantly to the seismic hazard in this region also. [54][55][56] Details of all the 200 recording sites considered in this study are given in Table A1 in Appendix A. The various columns from left to right in this table give the serial number, the full name and a three-character code, location in terms of latitudes and longitudes, elevation from mean sea level, number of three-component strong-motion records obtained, and the surface geology in brief for each of the strong motion recording sites.…”
Section: Seismotectonic Setup and Strong-motion Recording Sitesmentioning
confidence: 99%
“…Gupta and Trifunac 14 The NCR is also vulnerable to seismic hazards due to earthquakes in the western Himalayas and the HKS sources, in addition to local earthquakes in close proximity. The three different types of seismic sources considered to contribute to the NCR seismic hazard are described by separate path-dependent attenuation of PSV amplitudes similar to that in Gupta et al 5,6 for the seismic microzonation of NCT of Delhi. This has helped in developing a very realistic characterization of the spatial variation in the seismic hazard due to seismicity alone.…”
Section: The Study Areamentioning
confidence: 99%
“…The seismic sources and spatial distribution of the seismic activity parameters used in this study are the same that Gupta et al 5 detailed and used for the microzonation of the Delhi metropolitan area. 6 The modeling of the seismic activity for the local seismic sources covering the intraplate NCR area and its vicinity, as well as the north-western Himalaya (NWH) plate boundary sources is described in Section 4, while those of the HKS source at distances of about 1000 km is described in Section 5 of Gupta et al 5 The method of describing seismicity is similar to that reported in Lee et al, 7,8 Lee and Trifunac, 9,10 and Gupta et al 11 The path-dependent attenuation of spectral amplitudes has been accounted realistically using scaling equations based on attenuation models developed using strong motion data recorded from local events in the NCR of India, 12 events in the western part of the Himalayan Plate Boundary region recorded within the Himalaya and the adjacent Gangetic plains, 13 and from deep events in the HKS zone recorded at very long distances of around 1000 km in western Himalaya. 14 Lacking both the exact and detailed information on the local geological and soil site parameters to incorporate directly into the hazard computation, we have generated zoning maps of NCR for nine possible combinations.…”
Section: Introductionmentioning
confidence: 99%